Pengaruh Penerapan Sistem Manajemen Sumber Daya Perusahaan (ERP) dalam Meningkatkan Kinerja Manajemen Rantai Pasok (SCM) CV Sumber Cipta Agung - Ela Rahmawati; Fellia Rivanti; Fiona Fiona; Herman Herman; Kelvin Yovanka; Prissilia Angelika; Rizni Aulia Qadri; Immanuel Zai (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2023)
At this time, business is very easy to do because there are already systems that help the development of a business. There are several examples of business development systems, one of which is an ERP (Enterprise Resource Planning) system. With this system, it can help entrepreneurs to make a business plan so that it can run more effectively and efficiently. In addition to making business more effective and efficient, this system can also be combined with SCM (Supply Chain Management) so that these businesses can maximize the company's performance. There are lots of companies that use this ERP system, for example, CV Sumber Cipta Agung, which is engaged in producing food and beverages. CV Sumber Cipta Agung is a company engaged in the field of beverage manufacturers in the city of Batam which uses this system in developing its company to improve supply chain management (SCM) performance. The method used in this study is the method of interviews and literature review. CV Sumber Cipta Agung conducts its resource planning using SAP software and manages its supply chain system using the cross docking method.